(untitled) (European Journal of Behavioral Sciences, 2024)
This study investigates emotional resilience, social support, and coping mechanisms among male Persons Deprived of Liberty (PDL) experiencing grief in a district jail in Surigao del Sur, Philippines. In-depth interviews were conducted with three male detainees using a semi-structured interview guide. Data were analyzed using thematic analysis (Braun & Clarke, 2021), involving complete coding to capture relevant data, followed by identifying significant statements, emerging concepts, subcategories, categories, and themes. Thematic tables were used to organize findings, and both within-case and cross-case analyses were performed. Three key themes emerged: individual adaptive responses, impact of interpersonal connections, and grief management techniques. Common grief symptoms—somatic, emotional, and behavioral—were heightened by incarceration. Despite these challenges, participants showed emotional resilience, shaped by personality traits and past experiences, demonstrating adaptability, emotional regulation, and acceptance. Social support, primarily from family and jail staff, provided informational, instrumental, and emotional aid, but barriers like stigma and limited awareness hindered access to resources. Coping mechanisms included problem-focused and emotion-focused strategies such as humor, religion, and purposeful activities, emphasizing the need for personalized support. A psychological intervention program grounded in Acceptance and Commitment Therapy (ACT) is proposed to address grief among PDLs. The study recommends longitudinal research and program evaluations to improve support for grieving detainees.